The Right to Education in Human Rights Governance and Politics: Reporting and Monitoring Intercultural Education - Eva Gamarnikow (Universidad Autónoma de Madrid, 2016)
The right to education, as outlined in the Convention on the Rights of the Child (CRC) 1989, recognises the increasing multiculturalism of nation states and obligates governments to reform national curricula to reflect these changes, and to report on national education policies and practices to the Committee on the Rights of the Child. The aim of this paper is to explore European state responses to the human rights obligation to develop multicultural or intercultural education. It draws on the periodic reports submitted to the Committee on the Rights of the Child to analyse European state discourses on growing multiculturalism and educational change. The focus of the argument is on the discursive tensions and ambiguities in state education policies produced by the contradictory imperatives of national education systems, historically committed to transmitting national identity, and of intercultural education, as set out in article 29 of the CRC. These tensions are also be explored in the international human rights arena of political accountability, the Committee on the Rights of the Child, where national periodic reports on policy enactment are monitored through discussion and ensuing recommendations. The paper concludes by arguing that the tensions between national sovereignty and increasing multiculturalism of nation states result in intercultural education policy being constructed as exceptional and ephemeral.